Phase Behavior of Aqueous Biphasic Systems with Choline Alkanoate Ionic Liquids and Phosphate Solutions: The Influence of pH - Paula Berton; Hongzhe Tian; Robin D. Rogers (Molecules, 2021)
Aqueous biphasic systems (ABS) composed of the choline alkanoate ionic liquids (ILs) choline acetate [Cho][OAc], choline propanoate [Cho][Pro], choline butyrate [Cho][But], and choline hexanoate [Cho][Hex], mixed with K3PO4 solutions at pH 7.2 and 14.5, were prepared and their phase diagrams were compared. The ability to form ABS with alkaline K3PO4 solutions decreased in the order [Cho][OAc] ≈ [Cho][Pro] > [Cho][But] > [Cho][Hex], while with neutral K3PO4 solutions, [Cho][OAc] could not form an ABS, and the other three ILs performed similarly. All of the biphasic regions of the ABS decreased with the increase in pH. 1H-NMR data indicated anion exchange between phases in ABS at neutral pH. The ABS at neutral pH were evaluated to extract the triazine herbicides simazine, cyanazine, and atrazine, and the ABS formed by [Cho][Pro] and the pH 7.2 K3PO4 solution has shown extraction recoveries higher than 90%.